Stability and Volumetric Properties of Colored Asphalt Mixtures Containing Iron Oxide - Naji, Samer Ali; Abed, Alaa H. (Al-Nahrain Journal for Engineering Sciences, 2021)
The objective of this paper is find the effect of using iron oxide as a filler on the Marshall stability, flow and the volumetric properties of HMA and compared the results with conventional HMA using limestone dust. Three blends were used: coarse, mid and fine with neat bitumen (AC 40-50). One aggregate type (crushed) with two types of fillers: limestone and iron oxide III (?- ) with three different filler content 6%, 8% and 10%. The Marshall mix design was conducted on the three blends and the optimum binder content is computed for each blend. The Marshall stability test results and the volumetric properties analysis showed that increasing the iron oxide content from 6% to 10%  increases the stability about 28%, 17% , 16% for the coarse , mid and fine mixtures respectively. This increment in stability of mixtures using iron oxide related to the increment in specific gravity of the mix (Gmb) by (1.3% to 1.5% about 30 to 50 kg/m3). On the other hand, the flow of mixtures is decreased about (5%) for mixes using iron oxide than the ones that used limestone as filler. The fine blend with 10% iron oxide exhibit the highest stability of 13.3 kN. While the coarse blend stability was 10 kN for the same filler type and content. Generally, the Marshall Test results of HMA using iron oxide as filler showed better resistance to plastic deformation, also produce denser HMA with higher stiffness. On the other hand, the volumetric properties analysis showed lesser values as compared with conventional mixture where the void in mineral aggregates and void filled with asphalt has decreased but within the acceptable limits.